Effects of a number of players on passing performance in a small-sided soccer game - Nakayama, M.; Miyazaki, J. (7th World Congress on Science and Football (WCSF), 2011, 2011)
The use of various task conditions in training brings about a difference in terms of a quality of soccer performance. The task conditions are useful operational measures for soccer coaches in order to make effective instructions. In this study, a number of players was focused as a task condition in a small-sided game. Therefore, the purpose of the study was to analyze the relationships between the number of players as a task constraint and a passing skill performance in a small-sided game. Methods The participants consisted of high school soccer club players. They performed thirty sets of two minutes games with three different conditions by changing number of players (4v4, 5v5 and 6v6) in double-boxed pitch size (33M×40M). The ordinary soccer goals were used and goalkeepers were also included in the game. The games were recorded using video cameras to count the number of passes, the percentage of successful passes, and also duration of each pass. Results & Discussion There was no difference in terms of the total number of passes among the three conditions. This means that as the number of players increased, it decreased the number of passing opportunities for players. In addition, there appeared to be a significant difference in averaged duration of passes in some conditions. As a number of players increased, it shortened the duration of pass. It could be said that the averaged duration of a pass is related to the distance of the pass, i.e., long duration of a pass would be considered as the long distance pass. These results implies that coaches should be aware of these results which influence the players` performance level and be able to apply them in relation to the purpose of the training. Conclusion This study proved that the number of players influences passing skill performance in a small-sided game. Changing number of players in a same pitch will change the player-player distance, and also changed the duration of passes significantly. Thus, coaches should make a purpose of taining clear, and also to achieve that purpose, they should manipulate the task conditions appropriately, for instance, the pitch size and a number of players.